Magnetic nanoparticles and ionic liquid effect on electrochemical sensors performance (Rudarsko-geološko-naftni zbornik, 2022)
Magnetic nanoparticles and ionic liquid (IL, 1-hexyl-3-methyl-imidazolium bromide) based on graphene oxide (GO) composite provide unique physical and chemical properties in electrochemical sensors performance. Magnetic nanoparticles can cover active sites that increase chemical reactions with easy separation. IL increases the scan rate of electron transfer between the modified electrode and solution because it includes conductive adhesion properties. Also, IL in the next steps of design carbon paste electrodes (CPE) increases the cohesion. The study aims are to study the effects of magnetic nanoparticles and IL on the electrochemical detection of dopamine (DA). DA has a vital role in the mammalian central nervous system and change its value from the standard range leads broad mental diseases. But magnetic graphene oxide (MGO) may not exist capable of enhancing electrochemical signs alone. In this regard, after the synthesis of MGO, IL was established on composite. Then gold nanoparticles (AuNPs) and molecularly imprinted polymer (MIP) were modified MGO nanocomposite. MIP polymerization was continued by methacrylic acid (MAA) in the presence of DA as a template molecule. The developed sensor with modified nanocomposite studied by cyclic voltammetry (CV) and differential pulse voltammetry (DPV) techniques. The modified sensor based on nanocomposite with a broad concentration linear range, between 1×10-7 to 1×10-4 M and a limit of detection of 1×10-8 M (S/N=3) was used for the detection of DA in biological samples. Furthermore, these results prove that MGO was improved active sites of surface nanocomposite and IL was increased conductivity in the based electrochemical sensor for DA detection.